2021
DOI: 10.3390/pharmaceutics13050740
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug Interaction between Tofacitinib and Voriconazole in Rats

Abstract: Fungal infections are prevalent in patients with immune diseases. Voriconazole, a triazole antifungal drug, inhibits the cytochromes CYP3A4 and CYP2C, and tofacitinib, a Janus kinase inhibitor for the treatment of rheumatoid arthritis, is metabolized by CYP3A4 and CYP2C19 in humans. Here, we investigated their interaction during simultaneous administration of both drugs to rats, either intravenously or orally. The area under the plasma concentration–time curve from time zero to time infinity (AUC) of tofacitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Voriconazole was often used to prevent or treat posttransplant fungal infections 56,57 . It was a strong inhibitor of CYP3A4 58–60 . Several studies found that voriconazole noticeably raised the drug concentration of tacrolimus 58,60–62 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Voriconazole was often used to prevent or treat posttransplant fungal infections 56,57 . It was a strong inhibitor of CYP3A4 58–60 . Several studies found that voriconazole noticeably raised the drug concentration of tacrolimus 58,60–62 .…”
Section: Discussionmentioning
confidence: 99%
“…56,57 It was a strong inhibitor of CYP3A4. [58][59][60] Several studies found that voriconazole noticeably raised the drug concentration of tacrolimus. 58,[60][61][62] However, the combination of voriconazole did not significantly affect the PK of tacrolimus in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation